1988
DOI: 10.1104/pp.88.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Active Transport of Inorganic Carbon Increases the Rate of O2 Photoreduction by the Cyanobacterium Synechococcus UTEX 625

Abstract: Chlorophyll a fluorescence ofSynechococcus UTEX 625 was quenched during the transport of inorganic carbon, even when CO2 rfxation was inhibited by iodoacetamide. Measurements with a pulse modulation fluorometer showed that at least 75% of the quenching was due to oxidation of QA, the primary acceptor of photosystem II. Mass spectrometry revealed that transport of inorganic carbon increased the rate of 02 photoreduction. Hence, 02 could serve as an electron acceptor to allow oxidation of QA even in the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 21 publications
(31 reference statements)
4
45
0
Order By: Relevance
“…Bicarbonate accumulation in the cytoplasm is thought to have an ATP : HCO K 3 or NADH : CO 2 cost ratio of 1 (but see Ritchie et al 1996). This ATP demand for CCM operation can be supplied directly by thylakoid pathways described in §5 (figure 6), including the pseudocyclic pathway (Mehler; Miller et al 1988;Sü ltemeyer et al 1993). Rubisco levels are also elevated under low CO 2 conditions to overcome slow catalytic rates (Tortell et al 2000), representing an additional resource cost to the cell.…”
Section: Nutrientsmentioning
confidence: 99%
“…Bicarbonate accumulation in the cytoplasm is thought to have an ATP : HCO K 3 or NADH : CO 2 cost ratio of 1 (but see Ritchie et al 1996). This ATP demand for CCM operation can be supplied directly by thylakoid pathways described in §5 (figure 6), including the pseudocyclic pathway (Mehler; Miller et al 1988;Sü ltemeyer et al 1993). Rubisco levels are also elevated under low CO 2 conditions to overcome slow catalytic rates (Tortell et al 2000), representing an additional resource cost to the cell.…”
Section: Nutrientsmentioning
confidence: 99%
“…When CO, fixation was inhibited by IAC or glycolaldehyde, net O, evolution was not observed, but the C,-stimulated rates of O, evolution and O, reduction were nearly equal to the rates of O, evolution observed with C,-saturated photosynthesis (Miller et al, 1988). The occurrence of photochemical quenching with O, photoreduction when CO, fixation was inhibited clearly indicated that linear electron transport was stimulated by the development of the intracellular Ci pool (Miller et al, 1991;Badger and Schreiber, 1993).…”
mentioning
confidence: 77%
“…Calibration for CO, was performed by injecting small amounts of K,',C03 in the stoppered cuvette in BTP/HCl buffer and calculating the equilibrium concentration of CO, at 30°C and pH 8 (Miller et al, 1988). The mass spectrometer was also calibrated by injecting the K,CO, into 0.2 N HC1 in the reaction cuvette.…”
Section: Msmentioning
confidence: 99%
See 2 more Smart Citations